Association of acute kidney injury defined with the AKIN criteria and poor outcome in acute respiratory distress syndrome patients - Mohamed H. Saleh; Mohamed O. Elghonemi (The Egyptian Journal of Bronchology, 2017)
Abstract Background Few studies have reported the deleterious association between acute respiratory distress syndrome (ARDS) and acute kidney injury (AKI). We aimed to evaluate the association of AKI and poor outcome in ARDS patients and whether this association is related to fluid overload or not. Patients and methods Sixty-four patients diagnosed with ARDS and had been mechanically ventilated were enrolled. AKI was diagnosed using the Acute Kidney Injury Network criteria. Patients were stratified into two groups according to the degree of renal impairment. All data were statistically analyzed. Results The mean age of the studied patients was 47.23 ±10.12 years; 33 (51.6%) were men. In group 2, the follow-up Lung Injury Severity Score and length of hospital stay were significantly higher compared with group 1: 3.33±0.74 points and 19.11±6.37 days versus 2.84±0.57 points and 12.38 ±4.21 days (P=0.004 and <0.001, respectively). Also, they had higher need to use vasoactive (VA) agents, 21 (55.3%) versus 6 (23.1%) patients, and spent more days on mechanical ventilation, 14.18±4.59 versus 8.51±3.77 (P=0.019 and <0.001, respectively). In-patient mortality was higher in group 2 compared with group 1: 18 (66.7%) versus 6 (23.1%) (P=0.019). In-patient mortality was significantly correlated with the need to use VA agents and higher cumulative fluid balance (R=0.394 and 0.24, P=0.001 and 0.05, respectively). The need to use VA agents was the only independent predictor of mortality (odds ratio=4.18, P=0.022). Conclusion AKI as defined on the basis of the Acute Kidney Injury Network criteria is associated with poor outcome in ARDS patients. Egypt J Bronchol 2017 11:327–331